Reliability of FEM in analysing composite structures. (4th August 2014) - Autio, M.; Parviainen, H.; Pramila, A.
In the present study the reliability of FEM in analysing composite structures has been considered. The results given by composite elements of commercial FEM–programs have been compared with reference solutions in several plate cases. The accuracy, which can be achieved in analysing real structures by FEM, has been studied by comparing results of the FEM–model with measured results. Usually errors of results given by FEM–programs were less than 10%. However, in some cases even using dense mesh the error was about 25%. The difference between FEM–results and measured results was about 20%.